Inovasi Pembelajaran Berbasis Proyek (Project Based Learning) di SDI As-Syafi’ah - Hanik Nur Naila; Angga Nuraufa Zamzami Saputra; Fuadillah Ali Sofyan; Inchinia Angger Rowin; Mohamad Sodik (Mathematics Education Study Program, 2024)
Elementary education apparently requires innovation to improve the quality of its learning. Considering that we have now entered the modern era, where students are increasingly modern. They are more interested in real things, not just material things. And considering that it is now easy to access information from cyberspace where elementary school children can easily access it. Project Based Learning, it aims to develop the skills of elementary school students. This innovation focuses on developing projects when learning is designed to stimulate student creativity and foster collaborative attitudes among them. With this step, students not only improve their academic skills, but can also improve social skills that affect their attitudes when learning. This study collaborates with the implementation of the project-based learning (PjBL) model, focusing on evaluation and its impact on students' creative and collaborative skills. The evaluation method of this research was carried out through a case study at SDI As-Syafi'ah using project assessments, and interviews with teachers. The results of the research findings found a significant increase in the level of student creativity, as well as the development of their ability to work effectively in groups. The basic concept of innovation in teaching and learning activities is expected to encourage students' ability to explore interests, ideas or concepts, creative solutions, and to work together in teams. The real impact can open up discussions about the use of modified and appropriate models in the elementary school curriculum to further improve students' abilities in facing the demands of the times and contribute or play a role in the effectiveness of project-based learning resource innovation to improve creative and collaborative skills at the elementary school level.